The rule of five should not impede anti-parasitic drug development. Issue 2 (August 2017) - McKerrow, James H.; Lipinski, Christopher A.
Abstract: The "rule of 5" has become a mainstay of decision-making in the pharmaceutical industry as well as in nonindustrial (academic and institutional) drug development. However the authors of the original paper never intended for "double cutoffs" to preclude development of new drug leads for parasitic diseases. Graphical abstract: Highlights: "rule of 5" is a mainstay of decision-making in drug screening efforts. Acts as an absorption-permeability alert procedure to guide medicinal chemists. Never intended to apply to parasitic infectious diseases. Should not impede anti-parasitic drug development.